Analisis Perbandingan Implementasi Metode MADM dan Fuzzy MADM SAW Pada Sistem Pendukung Keputusan - Agus Sidiq Purnomo; Anief Fauzan Rozi (Faculty of Computer Science, University of Jember, 2022)
There are so many studies that use the Multi-Attribute Decision Making (MADM) method as a solution in Decision Support Systems. In addition, there are also many studies that use additional fuzzy which is implemented in the MADM method which is commonly referred to as Fuzzy MADM. For example, using Simple Additive Weighting (SAW), which one is closer to the best solution, whether to use MADM SAW or FMADM SAW, which one is better to use. Based on these problems, in this study analysis will be carried out regarding which method is closer to the best solution to be implemented in the case of Decision Support System between MADM and FMADM, in this case using the case of selecting the best graduates in the study program and the SAW method. Based on the results of the discussion in this study, it can be concluded that the implementation of MADM uses SAW, with 2 approaches, namely: Likert and fuzzy scales. The results obtained from the comparison of assessment ranges using the Likert and fuzzy scales obtained suitability of 100%. While the results of testing using RSD on Likert and fuzzy scales obtained the same results, namely 12.24%. The use of a Likert scale or fuzzy numbers has no effect, what affects the results is the range of the rating scale.